Integration as a spatial institution: Implications for agglomeration and growth - Tim Deeken; Ingrid Ott (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2014)
In this article we analyze the interdependent issues of urbanization, growth, and globalization by presenting key empirical facts and relevant underlying economic theories on each. We look more closely, but without providing a detailed formal analysis, at a model by Baldwin and Forslid (2000) that combines a seminal model from the endogenous growth literature (Romer 1990) with one from the new economic geography literature (Krugman 1991). In the analysis the significance of a sophisticated consideration of the concept of integration is pointed out. We investigate the issue of scale, scale economies, and density and the important role integration plays in these considerations as well. We especially argue that future research should more precisely focus on integration as a dynamic concept that does not only affect agglomeration and growth, but which is itself the endogenous outcome of various interdependencies and which complements the institutional settings of the territories that are linked to each other.
urn:nbn:de:swb:90-422265
Keywords: O4; R5; 330; integration; spatial institution; agglomeration; growth